2019
DOI: 10.3399/bjgpopen19x101675
|View full text |Cite
|
Sign up to set email alerts
|

Optimising Management of Patients with Heart Failure with Preserved Ejection Fraction in Primary Care (OPTIMISE-HFpEF): rationale and protocol for a multi-method study

Abstract: BackgroundHeart failure with preserved ejection fraction (HFpEF) is less well understood than heart failure with reduced ejection fraction (HFrEF), with greater diagnostic difficulty and management uncertainty.AimThe primary aim is to develop an optimised programme that is informed by the needs and experiences of people with HFpEF and healthcare providers. This article presents the rationale and protocol for the Optimising Management of Patients with Heart Failure with Preserved Ejection Fraction in Primary Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Interviews were conducted by three researchers (FF, MH, ES) who had established rapport with the interviewees through prior studies. (10)(11)(12) The same researchers familiarised, categorised and collated data into descriptive codes in an inductive approach; 50% of all interviews were double coded. All authors contributed to searching, reviewing and defining themes.…”
Section: Approachmentioning
confidence: 99%
“…Interviews were conducted by three researchers (FF, MH, ES) who had established rapport with the interviewees through prior studies. (10)(11)(12) The same researchers familiarised, categorised and collated data into descriptive codes in an inductive approach; 50% of all interviews were double coded. All authors contributed to searching, reviewing and defining themes.…”
Section: Approachmentioning
confidence: 99%
“…Characterising patients with HFpEF in primary care is an essential step towards improving diagnosis and management, as well as recruiting into trials. This analysis presents baseline data from a longitudinal observational study that is a component of the Optimising Management of Patients with Heart Failure with Preserved Ejection Fraction in Primary Care (Optimise HFpEF) study [14]. Patients were recruited based on a search of primary care HF registers for patients with no record of reduced ejection fraction.…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study revealed that specialist nurses can greatly improve the effectiveness of health education (14). By managing high-risk factors and regularly pushing health education content for stroke patients using mHealth equipment, patients can observe the trend chart of their blood pressure indicators, which can better provide alerts for them.…”
Section: Discussionmentioning
confidence: 99%
“…The BHHM can provide more timely professional health interventions, allowing patients to obtain a better healthrelated knowledge (13). In previous studies, an Ambulatory Blood Pressure Monitor Mobile Health System was established to enable a patient to be aware of their risk in real-time, and this has improved the medication adherence with risk self-management (14). In the present study, the BHHM-led mobile health for secondary stroke prevention was established for post-hospital stroke patients, in order to determine its effectiveness.…”
Section: Introductionmentioning
confidence: 99%